Cyberism: The theory for relationships between human and cyberspace - Huansheng NING (工程科学学报, 2025)
Approximately more than seven million years since early humans, humanity has existed within three fundamental spaces: physical (also known as the natural space), social, and thinking (also referred to as the cognitive space) spaces. The physical space represents the interaction between humans and the natural environment; the social space reflects the network of relationships among individuals; and the thinking space includes human consciousness, cognition, and the spiritual world. However, with the advent of electronic computers and the subsequent development of the internet and artificial intelligence, human status of production and living have undergone significant changes. A new space—cyberspace—has emerged beyond the original three fundamental spaces. This space not only encompasses human activities in the digital environment but also significantly influences identity construction, social behavior, value systems, and ideologies. New digital phenomena such as livestream commerce, the gig economy, metaverse, virtual humans, online education, and digital social interactions are rapidly expanding the dimensions of human life, leading to unprecedented behavioral patterns and social structures. In traditional Chinese culture, Confucianism studies the relationship between people (social space), Buddhism explores the relationship between individuals and their inner minds (thinking space), and Daoism (or Taoism) focuses on the relationship between humans and nature (physical space). However, the relationship between humans and cyberspace has not yet been thoroughly explored. In response to this significant transformation, this paper introduces the concept of Cyberism, a new school of thought developed as a counterpart to Confucianism, Buddhism, and Daoism. Cyberism is dedicated to systematically exploring the fundamental relationship between humans and cyberspace and establishing new principles for existence, behavior, and ethics within this digital realm. It views cyberspace not only as a technological extension but also as a full-fledged existential domain that demands its own philosophical, scientific, and normative framework. This study focuses on several fundamental issues in Cyberism. These include problems related to cyber philosophy, cyber science, and cyberlogic. It also examines questions concerning the notion of “the human” in Cyberism, such as cyborgs, digital humans, digital twin humans, and robots. Furthermore, it explores issues of technological development in Cyberism, including sense–communication–computation–storage, the transformation from data to intelligence (data–information–knowledge–intelligence), the progression from artificial narrow intelligence to artificial general and super intelligence (ANI–AGI–ASI), human–machine integrated intelligence, and artificial consciousness. This study also considers social and cognitive challenges, including cyber ethics and morality, culture and art, gender, psychology, and governance. Additionally, it discusses health and disease issues arising from existence in cyberspace. In addition, this paper elaborates on a disciplinary framework for Cyberism encompassing the natural, social, cognitive, and cyber sciences. Based on the cyber–physical–social–thinking (CPST) space, it outlines a new approach to disciplinary organization and highlights the transformation of traditional academic structures. Finally, it explores the challenges and opportunities that Cyberism presents for the evolution of human civilization, education, and technological innovation. Cyberism, as a pioneering field bridging humanities and cyberspace, offers not only a theoretical lens for navigating digital transformation but also a potential philosophical and ethical cornerstone for sustaining human dignity, purpose, and development in an increasingly virtualized world.